Effect of caffeine ingestion on resistance training performance - Silva, Vitor Loureiro (2014)
Caffeine –1,3,7 trimetilxanthine –is one of the most widely used as a ergogenic aid in sports scenario, with multiple actions on body, either central as peripheral. A great number of studies evaluated the effects of caffeine ingestion on endurance performance, with predominance of aerobic metabolism. However, data in scientific literature about the impact of caffeine ingestion on high intensity and short duration activities arescarce and equivocal. This studycomprises a systematic review on effects of caffeine intake upon strength training, discussing relevant aspects concerning its possible application to optimize strength-related sports performance and putative mechanisms of action. Articles were selected from Medline database, with the follow inclusion criteria: experimental studies (with control and experimental groups); double blind design; acute caffeine ingestion in a known dosage; utilization of dynamic strength exercises. Caffeine dosage varied between studies in a range of 179 mg to 6/g/kg of body weight (which represents 420 g in a average adult). The analyzed studies often show ambiguous results, which may be due to methodological issues. Some studies demonstrate a positive effect of caffeine ingestion on dynamic strength performance (1 repetition maximum strength and/or numberof repetitions to failure). Data pointed to a possible action of caffeine on perceptual responses, such as the rated perceived effort, despite some investigation do not corroborate this finding. Although more studies are necessary to clarify the efficacy of caffeine ingestion on strength performance, this strategy proves to be safe and do not represent risk to individuals.